Research on the performance of phase change energy storage devices based on solar energy - Ningge Xu; Chunlong Zhuang; Guangqin Huang; Hongyu Zhang; Fei Gan; Shanshan Hou; Lei Cheng; Yi Huang (PLoS ONE, 2025)
This article designs a high-altitude border guard post that can fully utilize the heat absorbed by solar collectors to continuously store thermal energy during the day and stably release heat at night. This device is a spherical encapsulated paraffin phase change heat exchanger device (stainless steel shell diameter: 80mm),By conducting thermal storage and release experiments on the device, the performance of the device was analyzed. The experimental results showed that in the thermal storage experiment, the outlet temperature of the hot fluid reached about 97 °C at about 500 minutes and tended to stabilize. The wall temperature and center temperature of the encapsulated paraffin sphere began to stabilize at about 450 minutes and stopped absorbing heat; In the heat release experiment, the wall temperature and core temperature of the encapsulated paraffin spheres stabilized at about 400 minutes and stopped releasing heat; In this way, it can meet the heating needs of storing heat for about 8 hours during the day and continuously releasing heat for 6.5 hours at night.